Regulation of Lipid Bilayer Ion Permeability by Antibacterial Polymethyloxazoline‐Polyethyleneimine Copolymers. (26th November 2020) - Kozon, Dominika; Bednarczyk, Piotr; Szewczyk, Adam; Jańczewski, Dominik
Abstract: Amphiphilic antimicrobial polymers display activity against the outer bacterial cell membrane, triggering various physiological effects. We investigated the regulation of ion transport across the lipid bilayer to understand differences in biological activity for a series of amphiphilic polymethyloxazoline – polyethyleneimine copolymers. The results confirmed that the tested structures were able to increase the permeability of the lipid bilayer (LB) membrane or its rupture. Black lipid membrane (BLM) experiments show that the triggered conductance profile and its character is strongly correlated with the polymer structure and zeta potential. The polymer exhibiting the highest antimicrobial activity promotes ion transport by using a unique mechanism and step‐like characteristics with well‐defined discreet openings and closings. The molecule was incorporated into the membrane in a reproducible way, and the observed channel‐like activity could be responsible for the antibacterial activity of this molecule. Abstract : Coming through : The black lipid membrane technique was used to investigate the membrane‐permeabilization abilities of a series of amphiphilic antimicrobial polymers. The most potent antibacterial polymer induces step‐like current behavior typical for an ion‐channel.